Concertation numérique et aménagement du territoire : coconstruction d’un outil expérimental d’e-débat - Sylvain Pioch; Hélène Rey Valette; Pierre-Yves Hardy; Camille Richebourg; Claire Ollagnon; Philippe Estival (Développement Durable et Territoires)
While there is a growing demand with participation and consultation from the public, relating to infrastructure projects or land planning, critics point out the inadequacy of these mechanisms. The low number, or even the absence, of certain profiles are often criticized by suggesting that the use of digital technology could overcome some of these limitations. The collaborative design of an experimental digital concertation platform, for land planner, provides an opportunity to analyze the conditions of digital participation. This experimentation helps to identify some of the contributions resulting from digital technology in terms of information, transparency and traceability. It also helps to explore few elements from the complementarity between face-to-face and digital debate mechanisms.